Peculiarities of using Artificial Intelligence in Conducting Administrative Court Cases - qizi, Oʻsarova Saodat Oʻtkir (Journal of Innovation in Education and Social Research, 2025)
Through this article you might have information about what is artificial intelligence and how to use it in the administrative court cases in Uzbekistan.